2+(-1)(7)=5(-1)

Simple and best practice solution for 2+(-1)(7)=5(-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+(-1)(7)=5(-1) equation:


2+(-1)(7)=5(-1)

We simplify the equation to the form, which is simple to understand
2+(-1)*(7)=5(-1)

Reorder the terms in parentheses
multiplication of parentheses
2+(-7)=5*(-1)



Remove unnecessary parentheses
+2-7=+5+*(-1+)

Reorder the terms in parentheses
2-7=+(-5)

Remove unnecessary parentheses
+2-7=-5

We move all terms containing to the left and all other terms to the right.
0=-5-2+7

We simplify left and right side of the equation.
0=0

0=0

This equation is an identity, so all real numbers are solutions.

 

See similar equations:

| 13x=20x^2-15 | | 5+15n-3=9n+86-6n | | 4x-6=x+11 | | -3(4)+7=2y+3 | | 9+16x=4(4x+3) | | 10x+9-11-x=-2(2x+4)+3(2x-2) | | 3(x-5)-4(12-x)=7 | | mk+mz=t | | y=3(-1)-5 | | N+4=-8 | | -18-57x+85x^2+100x^3=0 | | -7c=-21 | | 3/5(15)-(2/9)y=-13 | | 4x=.128 | | 3(4-z)-22=27z-5(2+6)z | | 2x-2=2(x+1) | | 4x=128 | | 2x^2-5x+2=(x-3)(x+2)+3x | | -1.5x=30 | | c^2-3c-10=0 | | (x+3)(2x-5)= | | 6x+9=-4x+29 | | -2.3m=10 | | 6f-5f=2 | | 5x+3=3x-7 | | 9x^3+-3x^2+-3x+1=0 | | a+4b-2a+7b= | | 9x^3+-3x^2+-3x=-1 | | 2x+18x+36x= | | (5v-6)(9+v)=0 | | -n+5+27n=0 | | 2(x+5)+2x=16 | | 0=.98b+0.02b-b | | 4z^2-9=0 | | -11.2+4(2.1+q)= -0.8 | | 2y^2+7-6=0 | | 2c+24=-2c-12 | | 2(1.5x+5)+2x=16 | | X^3+11x^2=0 | | e=kmc^2 | | 5m-2(m+2)=-(+15) | | 6x+1=6x-4 | | Y^2-12y=-23 | | x(25x^2-4)=0 | | 5x-5=125 | | 2(x+4)-5=3(x-2) | | 3x-2(x+1)+5=7 | | 7x+1=9x-1 | | 4y+16x=8 | | 20.5=15(d)/11 | | 20.5=15d/11 | | 5+3x=5x-1 | | -3x^2=-3x+8 | | 4e-3e-2=7-9 | | 7(6-2a)=(-3a+1) | | 4x-9=-7+2x | | 4e-3e-2=1-9 | | 3x+1-2x=5 | | 3a-2a+6-4+4a= | | s+1/3=-5/9 | | (8a+2)-(2a+6)= | | 7w+2=3+94 | | 6(x-6)+7=0 | | -3.2z=10-4.2z | | a+-2a= |